(untitled) (Web of Scientists and Scholars: Journal of Multidisciplinary Research, 2025)
This article discusses the issue of developing students’ creative potential through pedagogical technologies used in the educational process. Today, it is crucial to apply innovative approaches and modern technologies in education, encouraging students to think independently and to innovate. The role of pedagogical technologies in shaping creative thinking, their effectiveness, and methods of practical implementation are analyzed. Furthermore, the contribution of interactive methods, problem-based learning, project-based methods, reflective and critical thinking to the development of creative potential is explored. It is emphasized that the correct selection and effective application of pedagogical technologies guide students towards independent creativity, free expression of their ideas, and the creation of innovative projects. The results of this study contribute to the improvement of the educational system and the enhancement of students’ creative potential.